THE IMPACT OF VOCABULARY BREADTH AND DEPTH ON STUDENTS' PERCEPTION OF DIFFICULTY IN IELTS READING: A STUDY ON TEST ANXIETY AND COPING MECHANISMS - Nasichah, Alfi Hulwatun; Nursandy, Naillis Nabila (UHN IGB Sugriwa Denpasar, 2025)
This study investigates the relationship between vocabulary breadth and depth and students’ perceived difficulty in the IELTS Reading Test, as well as how these perceptions relate to test anxiety and coping mechanisms. Vocabulary breadth refers to the number of words known, while depth reflects how well each word is understood, including its synonyms, collocations, and contextual meanings. Thirty EFL learners from an English learning community in Kediri, Indonesia, participated in this quantitative descriptive study. Data were collected through a Likert-scale questionnaire distributed via Google Form, which explored students’ vocabulary knowledge, reading strategies, anxiety levels, and perceptions of reading difficulty. Data were analyzed using descriptive statistics and interpretive analysis to capture both numerical trends and underlying perceptions. The results indicate that while most participants demonstrated adequate vocabulary breadth, many still struggled with vocabulary depth particularly in recognizing paraphrases, collocations, and polysemous words. These lexical gaps were strongly linked to their perceived difficulty with synonym and paraphrase-based questions in the IELTS Reading section. Additionally, the majority of students reported experiencing anxiety when encountering many unfamiliar words, often relying on coping strategies such as contextual guessing or skipping sentences to maintain reading flow. However, panic triggered by lexical unfamiliarity remained a significant barrier to comprehension. Overall, the findings highlight that vocabulary depth, rather than breadth alone, plays a more critical role in reading comprehension and perceived difficulty. The study suggests integrating explicit depth-oriented vocabulary instruction with anxiety-reduction strategies to enhance students’ reading performance and test confidence